2010
DOI: 10.1155/2010/824976
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Diversity ofStreptococcus mutansin Caries-Free and Caries-Active Preschool Children

Abstract: Aim. The aim of the present paper was to evaluate the genotypic diversity of S. mutans in caries-free and caries-active preschool children in Brazil. Design. Twenty-eight preschool children were examined regarding caries experience by the dmft index. DNA from 280 isolates of S. mutans was extracted. S. mutans evaluated using to the PCR method, with primers for the glucosyltransferase gene. The genetic diversity of S. mutans isolates was analyzed by arbitrary primed-PCR (AP-PCR) reactions. The differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 28 publications
10
32
0
1
Order By: Relevance
“…No significant difference was observed between the number of genotypes and sex, which is consistent with other studies (Liu, Zou, Shang and Zhou, 2007, Pieralisi, Rodrigues, Segura, Maciel, Ferreira, Garcia and Poli-Frederico, 2010). Li and Caufield previously reported that female infants are more likely to share genotypes with their mothers than male children (Li and Caufield, 1995).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…No significant difference was observed between the number of genotypes and sex, which is consistent with other studies (Liu, Zou, Shang and Zhou, 2007, Pieralisi, Rodrigues, Segura, Maciel, Ferreira, Garcia and Poli-Frederico, 2010). Li and Caufield previously reported that female infants are more likely to share genotypes with their mothers than male children (Li and Caufield, 1995).…”
Section: Discussionsupporting
confidence: 93%
“…However, our finding that children with multiple genotypes were about 4.5 times more likely to have caries than children with a single genotype (Table 2) is consistent with more recent reports using AP-PCR and multilocus enzyme electrophoresis (Alaluusua and Matto, 1996, Gamboa, Chaves and Valdivieso, 2010, Napimoga, Kamiya, Rosa, Rosa, Hofling, Mattos-Graner and Goncalves, 2004, Pieralisi, Rodrigues, Segura, Maciel, Ferreira, Garcia and Poli-Frederico, 2010, Zhao, Li, Lin, Chen and Yu, 2014, Zhou, Qin, Qin and Ge, 2011). This is the first report of this association using rep-PCR and combined with the findings of the recent studies would seem to suggest that having multiple S. mutans genotypes may be an important factor in dental caries development.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations